2021
DOI: 10.1002/jemt.23797
|View full text |Cite
|
Sign up to set email alerts
|

Employing machine learning and microscopy images of AIB1‐stained biopsy material to assess the 5‐year survival of patients with colorectal cancer

Abstract: Our purpose was to employ microscopy images of amplified in breast cancer 1 (AIB1)‐stained biopsy material of patients with colorectal cancer (CRC) to: (a) find statistically significant differences (SSDs) in the texture and color of the epithelial gland tissue, between 5‐year survivors and non‐survivors after the first diagnosis and (b) employ machine learning (ML) methods for predicting the CRC‐patient 5‐year survival. We collected biopsy material from 54 patients with diagnosed CRC from the archives of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…IHC slides stained for pan-cytokeratin from patients with pT3 and pT4 colon ADC were used to train a DCNN to predict the occurrence of distant metastasis based on tumor architecture [100]. Another study showed that IHC-stained images of the amplified breast cancer 1 (AIB1) protein from CRC patients could operate as a predictive 5-year survival marker [101].…”
Section: Histological Features Related To Prognosis Metastasis and Su...mentioning
confidence: 99%
See 1 more Smart Citation
“…IHC slides stained for pan-cytokeratin from patients with pT3 and pT4 colon ADC were used to train a DCNN to predict the occurrence of distant metastasis based on tumor architecture [100]. Another study showed that IHC-stained images of the amplified breast cancer 1 (AIB1) protein from CRC patients could operate as a predictive 5-year survival marker [101].…”
Section: Histological Features Related To Prognosis Metastasis and Su...mentioning
confidence: 99%
“…The most common pre-trained model used for CRC is based on the VGG architectures. Four of the studies, presented by Zhao et al [95,97], Xu et al [76] and Jiao et al [70], employed the VGG-19, while two of the studies employed the VGG-16 [41,101]. Furthermore, two other studies compared different parameters of the general VGG architecture [38,80].…”
Section: Popular Architectures With Transfer Learningmentioning
confidence: 99%